THE EFFECT OF STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) STRATEGY ON THE READING COMPREHENSION OF THE SECOND YEAR STUDENTS OF SMAN 1 BENAI - Nisa Ulkhaira Erzag; Fadly Azhar; Dahnilsyah Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to find out the significant effect of STAD strategy on the reading comprehension of the second year students of SMAN 1 Benai academic year 2018/2019. The selected sample was XI MIPA 1 students which consisted of 35 students. The sample was selected by using random sampling technique. This research used pre-experimental research design of one group pre-test post-test and collected the data by using tests on analytical exposition text. The test of this research was multiple choice test consisted of five options (A/B/C/D/E). The result of the study was found that the mean score of pre-test was 46.14 while the post-test was 61.03. Therefore, it can be concluded that there is a signifant effect of STAD strategy on the reading comprehension of the second year students of SMAN 1 Benai. In other words, teaching reading comprehension through STAD strategy is an effective way to solved the students’ problem on the reading comprehension.Keywords: Effect, STAD strategy, reading comprehension.